2020
DOI: 10.1111/jiec.13078
|View full text |Cite
|
Sign up to set email alerts
|

Symbiosis opportunities between food and energy system: The potential of manure‐based biogas as heating source for greenhouse production

Abstract: The concept of symbiosis, a mutually beneficial relationship, can be applied to food and energy systems. Greenhouse systems and biogas plants are interesting technologies for food–energy symbiosis, because both are usually based in rural areas and offer opportunities for the exchange of materials (e.g., biomass waste from the greenhouse as input to biogas plants) and energy (heat from biogas co‐generation for heating greenhouses). In this paper, the focus lies on manure resources for biogas in Switzerland, bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The country energy demand could be reduced and efficient energy use can be optimized (SCCER CREST, 2020). Other important aspects need to be considered, for example, the food‐energy‐nexus for agricultural bioenergy (Burg et al, 2020; Christensen & Kjaer, 2009) which allows symbiosis between food production and energy generation. Moreover, one area can have multiple purposes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The country energy demand could be reduced and efficient energy use can be optimized (SCCER CREST, 2020). Other important aspects need to be considered, for example, the food‐energy‐nexus for agricultural bioenergy (Burg et al, 2020; Christensen & Kjaer, 2009) which allows symbiosis between food production and energy generation. Moreover, one area can have multiple purposes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The development of an incineration plant, which will incinerate manure to generate energy, has been proposed as a solution to poultry manure surplus in the Netherlands [30]. Manure can be used as a feedstock for biogas plants, and the waste heat for the plant can be supplied to local greenhouses [31]. It can also be used as a fertiliser, by being discharged to arable lands [32].…”
Section: Meat and Poultry Industrymentioning
confidence: 99%
“…In 2017, an F. oxysporum fungal outbreak infected pepper greenhouses in Essex County, Ontario, resulting in major plant loss; in a single example, one greenhouse operation experienced over 12% pepper mortality [35] (pp. [121][122][123][124][125][126][127][128][129][130][131][132]. One challenge with many crop pathogens is their largely undetectable presence at early stages of infection, allowing mitigation only after significant crop damage has occurred [36] (pp.…”
Section: Challenges Facing the Canadian Greenhouse Industrymentioning
confidence: 99%
“…Some operations use waste heat from nearby factories or biogas generators from adjacent farms, and implementation of confluent air jet climate control systems is being explored commercially [122]. Research has also indicated the potential for heating greenhouses using manure-based biogas where it is expected that up to 11% of the Swiss tomato demand could be supplied domestically in this manner [127]. Icelandic greenhouse operations have been reported to harness geothermal heat to extend their growing season [123].…”
Section: Global Greenhouse Development Initiativesmentioning
confidence: 99%